(untitled) - Day, John W. (America, 1989)
This text/reference covers estuarine ecology, providing a concise synthesis of information on the structure and function of these key ecosystems critical to the life cycles (especially breeding) of fish and other aquatic animals. Readable and basic enough to be used as text, it is also detailed and thorough enough to serve as a standard reference. Covers physical and chemical aspects of estuaries, the biology and ecology of key organisms, the flow of organic matter through estuaries, and human interactions, such as the environmental impact on estuaries of fisheries.
Các hệ sinh thái thủy vực
Keywords: Estuarine ecology